A National Strategy in Achieving English Communicative Ability: Globalisation Perspectives - Nuril Huda (Universitas Negeri Malang, 2016)
The vital role of English as an instrument to speed up national development justifies substantial efforts to improve the instruction. Learners of English in Indonesia suffer from difficulties since the language environment does not support them. Compensating tha lack of environment does not support them. Compensating the lack of environmental support with good quality of English instrustion in the primary and secondary schools would need a huge budget that the Government could not afford. Therefore, the target of the efforts should be limited to a smaller but more prospective population: university students